2011
DOI: 10.1149/1.3635659
|View full text |Cite
|
Sign up to set email alerts
|

PtNb Deposited on High Surface Area Carbon Support as Catalyst for Ethanol Electroxidation

Abstract: Platinum-niobium catalysts have been proposed as alternative catalysts for ethanol electro-oxidation. Catalysts prepared by a combined alcohol-sodium borohydride reduction method showed crystal sizes in the range of 3-4 nm, with large amounts of niobium oxide, as TPR results confirmed. Platinum decorated on a mixture of Nb2O5 (amorphous and crystalline)/Vulcan XC-72R carbon black was also prepared , with similar crystal sizes. XANES region analyses showed a certain electronic effect in the case of the co-reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…By the Debye–Scherer equation based on the full-width at half-maximum of the PXRD patterns, the average particle sizes were estimated to be 3.6, 2.4, and 4.3 nm for Pt 3 Nb/BP2000, PtNb/BP2000, and Pt/BP2000, respectively, which indicated that metal aggregation under high temperatures could be suppressed by alloying. We noted that the crystalline Nb 2 O 5 phase was obtained when only NbCl 5 was used with an identical high-temperature H 2 reduction (Figure S1b). This result indicates that Pt played a crucial role in Nb reduction probably by the H 2 spillover effect, , which was confirmed by H 2 -temperature-programmed-reduction (TPR) tests (Figure S2).…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…By the Debye–Scherer equation based on the full-width at half-maximum of the PXRD patterns, the average particle sizes were estimated to be 3.6, 2.4, and 4.3 nm for Pt 3 Nb/BP2000, PtNb/BP2000, and Pt/BP2000, respectively, which indicated that metal aggregation under high temperatures could be suppressed by alloying. We noted that the crystalline Nb 2 O 5 phase was obtained when only NbCl 5 was used with an identical high-temperature H 2 reduction (Figure S1b). This result indicates that Pt played a crucial role in Nb reduction probably by the H 2 spillover effect, , which was confirmed by H 2 -temperature-programmed-reduction (TPR) tests (Figure S2).…”
Section: Resultssupporting
confidence: 60%
“…32−34 We noted that the crystalline Nb 2 O 5 phase was obtained when only NbCl 5 was used with an identical high-temperature H 2 reduction (Figure S1b). This result indicates that Pt played a crucial role in Nb reduction probably by the H 2 spillover effect, 26,35 which was confirmed by H 2 -temperature-programmed-reduction (TPR) tests (Figure S2). High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) observations showed that the metal nanoparticles were homogeneously dispersed over the whole C support without any large nanoparticles (Figure 1b).…”
Section: ■ Results and Discussionsupporting
confidence: 53%
See 1 more Smart Citation